Marine Compounds and Cancer - Sergey A. Dyshlovoy (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
In Western countries, cancer is among the most frequent causes of death. Despite striking advances in cancer therapy, especially by the so called "targeted agents", there is still an urgent need for new drugs in oncology. Hope comes from the marine environment, which is a rich source of natural compounds showing anti-cancer activity. To date, four marine cytotoxic substances, namely cytarabine, trabectidine, eribulin, and monomethyl auristatin E (as a drug-antibody conjugate named vedotin) have made it into clinical routine. Many more are in all phases of clinical testing, and a plethora of substances has already been examined for in vitro and in vivo activity. Interestingly, more and more precise research tools allow the dissection of the molecular mode of action of these cytotoxic substances, thereby uncovering the specific drug targets in cancer cells. This development will blur the edges between "targeted" and "untargeted" therapy, and will hopefully lead to a more directed use of cancer medicine (based on a molecular rationale of activity) in the future. This Topical Collection will cover the whole scope from agents with cancer-preventive activity, to novel and previously characterized compounds with anti-cancer activity, both in vitro and in vivo, and the latest status of clinical development from drug trials. Of note, compounds possessing pro-carcinogenic activity or mediating cancer cell survival are also within the scope of this Topical Collection. In addition, a special focus will be placed on current shortfalls and possible strategies to overcome obstacles in the area of marine anti-cancer drug development.